2016
DOI: 10.1007/s10522-016-9643-y
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms linked to mitochondrial uncoupling protein genes UCP2 and UCP3 affect mitochondrial metabolism and healthy aging in female nonagenarians

Abstract: Energy expenditure decreases with age, but in the oldest-old, energy demand for maintenance of body functions increases with declining health. Uncoupling proteins have profound impact on mitochondrial metabolic processes; therefore, we focused attention on mitochondrial uncoupling protein genes. Alongside resting metabolic rate (RMR), two SNPs in the promoter region of UCP2 were associated with healthy aging. These SNPs mark potential binding sites for several transcription factors; thus, they may affect expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Studies have found that genetic polymorphisms in the UCP3 gene were suggested to be associated with hand grip performances in the elderly population's skeletal muscle. This suggested that the uncoupling process was related to muscle metabolism/catabolism in the elderly [72,73]. In addition, there was evidence that UCP2, UCP3, and UCP4 affect the individual's chances of surviving up to a very old age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that genetic polymorphisms in the UCP3 gene were suggested to be associated with hand grip performances in the elderly population's skeletal muscle. This suggested that the uncoupling process was related to muscle metabolism/catabolism in the elderly [72,73]. In addition, there was evidence that UCP2, UCP3, and UCP4 affect the individual's chances of surviving up to a very old age.…”
Section: Discussionmentioning
confidence: 99%
“…In females, a different mechanism appears to be involved. Regulatory variants in UCP2 and UCP3 are associated with FI 34 , and this association is not found in males (Kim et al, 2016a). These two genes encode mitochondrial inner membrane proteins that are called uncoupling proteins.…”
Section: Metabolic Dimensions Of Biological Agementioning
confidence: 95%
“…The variation in UCP2 portends a switch in substrate utilized for respiration from glucose to glutamate (Vozza et al, 2014) as FI 34 increases. There is an interaction between RMR and a UCP3 variant in the positive association with FI 34 that indicates an intensification in respiration (Kim et al, 2016a), such that more energy is expended when FI 34 increases. The relevant variant of UCP3 is associated with a higher hazard ratio for mortality, which we will come back to later.…”
Section: Metabolic Dimensions Of Biological Agementioning
confidence: 99%
“…The impact of leptin on uncoupled respiration has also been reported animal trial and this affect adaptive thermogenesis [ 25 ]. In addition, genetic polymorphism in uncoupling proteins (UCP2/3) was associated with improvement of mitochondrial function in human [ 26 ].…”
Section: Discussionmentioning
confidence: 99%